PENGARUH KULTUR BUDAYA TERHADAP TINGKAT KEMISKINAN (STUDI KASUS: ADAT KAMETI DIKABUPATEN SUMBA TIMUR) - Yohana Ndjoeroemana, Rambu H Indah (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2017)
Culturally, Culture is one of the assets of ancestral heritage as the values of pride, especially if we return to Soemarjan theory which states adat as a form of problem solving, and then this value becomes very positive. But economically, of course this kind of activity along with rituals with various symbols and signs that must be passed, need a material of high value, if studied carefully, it will lead us to the conclusion that this is a social spending that affects public spending in that tribe embraced the culture. The phenomenon that occurs, has led people to become bounded in culture (bounded culture), where the community is caught in a rigid cultural bond. Economically, the cost of implementing adat is concrete to be one individual or household expenditure, very dangerous if the amount is far above income, investment or savings, while on the other side of the economy continues to run. Problems like this are very difficult and take time to overcome them. Because the culture that has been rooted in a particular society is difficult to change and even eliminated. For that, needed a way to minimize the culture that is not appropriate and find an alternative to the inappropriate elements are not fixed in the culture so as not to cause poverty.